Ce2O3/BiVO4 Embedded in rGO as Photocatalyst for the Degradation of Methyl Orange under Visible Light Irradiation - Damian C. Onwudiwe; Boitumelo M. Phadi; Opeyemi A. Oyewo (J, 2021)
A p–n heterojunction semiconductor structure composed of Ce3O4 and BiVO4 has been synthesized and then incorporated into reduced graphene oxide (rGO) by the hydrothermal method. The ternary composites were characterized by X-ray diffraction, transmission electron microscopy (TEM), scanning electron microscopy (SEM), electron diffraction spectroscopy (EDS), and UV–vis spectroscopy. The efficiency of the composites as photocatalysts was determined by studying the oxidative degradation of methyl orange in aqueous solution under visible light irradiation. The effect of parameters such as pH, catalyst loading, and concentration of the dye solution was examined in order to determine their influence on the photocatalytic activity of the composites. The composite incorporated into reduced graphene oxide presented the highest percentage (above 90%) in 2 h time, attributed to the effect of the increased surface area. The process of the enhanced photocatalytic activity has been discussed based on the energy band positions of the nanoparticles within the composite.